Analisis Pengaruh Lingkungan Kerja, Dan Beban Kerja Terhadap Kinerja Karyawan Melalui Stress Kerja Pada Karyawan PT Pelabuhan Indonesia IV (PERSERO) Cabang Merauke - Putri Inggrid Maria Risamasu (Musamus Journal of Business & Management, 2018)
This study aims to determine the effect of work environment, workload and work stress on employee performance at PT Pelabuhan Indonesia IV (Persero) Merauke Branch. The type of research used in this research is descriptive verification. The sample is 45 people, which is the entire population. Data collection methods used were interviews and questionnaires. Data were analyzed by path analysis model with Smart PLS 2.0 program to determine the relationship between variables. The results showed that partially the work environment has a positive and significant effect on performance, workload has a positive and significant effect on performance, work stress has a positive and significant effect on performance. For indirect influence, competence and influential workload positive and significant impact on employee performance through work stress at PT Pelabuhan Indonesia IV (Persero) Branch of Merauke. Keywords: performance, work environment, workload, work stress